Implementasi Manajemen Sumber Daya Manusia dalam Meningkatkan Mutu Tenaga Pendidik di SMK Miftahul Ulum Bandar Lampung - Eti Hadiati; Sela Kholidiani; Ryuzen Praja Tuala; Okvita Okvitaningrum (Universitas Negeri Yogyakarta, 2026)
This study aims to analyze the implementation of human resource management strategies in improving the quality of educators at SMK Miftahul Ulum Bandar Lampung. The method used is a descriptive qualitative approach, utilizing data collection techniques through in-depth interviews, participant observation, and documentation involving the principal, student affairs staff, and teachers. The results of the study indicate that the school successfully implements a hybrid management model that harmonizes professional competency standards with Islamic boarding school values. Key aspects of this implementation include a recruitment system that balances foundation loyalty with strict micro-teaching testing, and adaptive competence development strategies to overcome facility limitations through industry partnerships and digital training. Furthermore, academic supervision is conducted using a humanistic approach to provide constructive feedback, while the internalization of religious values fosters a disciplined work culture and a strong sense of belonging (rasa kegondolan). This study concludes that integrating professional human resource management with spiritual values is effective in producing high-quality, adaptive, and character-driven educators. These findings serve as a reference for vocational education practitioners in managing limited resources to achieve superior educational quality.